Raman spectroscopy a promising technique for investigations of metallothioneins. - Torreggiani, Armida; Tinti, Anna (Metallomics : integrated biometal science, 2010)
Metallobiomolecules are highly elaborated coordination complexes, and their fundamental metal-ligand interactions are critical components of metalloprotein folding, assembly, stability, electrochemistry, and catalytic function. Herein, we have described the benefits in using Raman spectroscopy to define the metal-ion binding properties of MTs toward metal ions such as Zn(ii) and Cd(ii). In particular, this vibrational technique can shed light on the secondary structures eventually present in MTs and the ligands involved in metal coordination. The oxidation state of Cys residues and their participation in the metal chelation can be clearly defined, as well as the eventual involvement of His residues. With regards to exogenous metal ligands such as sulfide anions, their presence can be identified by some marker bands whose intensity is linearly correlated with sulfide/metal molar ratio. Finally, Raman can be also an useful tool for providing information on the favourite sites of the radical attack and radical-induced modification in protein folding. In conclusion, many advantages such as the capability of defining local regions in large complexes and detecting several structural features at the same time, the ability in supporting mechanisms, as well as the requirement of low sample amount, make to propose Raman spectroscopy, in coupling with analytical techniques such as atomic emission spectroscopy, gas chromatography, and circular dichroism, as one of the most promising experimental strategies in the research on structure-activity relationships in MTs.
Keywords: copper; Copper: chemistry; Copper: metabolism; metallothionein; Metallothionein: chemistry; Metallothionein: metabolism; Spectrum Analysis, Raman; Spectrum Analysis, Raman: methods; Structure-Activity Relationship; Zinc; Zinc: chemistry; Zinc: metabolism